Analyses of planetary boundary layer from remote sensing systems - Moreira, Gregori de Arruda (2018)
The Planetary Boundary Layer (PBL) is a relevant part of the atmosphere with a variable extension that clearly plays an important role in fields like air quality or weather forecasting. Passive and active remote sensing systems have been widely applied to analyze PBL characteristics. The combination of different remote sensing techniques allows obtaining a complete picture on the PBL dynamic. In this study, we analyze the PBL behavior using four types of remote sensing systems: Microwave Radiometer (MWR), Elastic Lidar (EL), Doppler Lidar (DL) and Ceilometer data. The measurements were performed in two cities Granada (Spain) and São Paulo (Brazil). Firstly, at Granada, the PBL height (PBLH) obtained from MWR data is validated against PBLH provided by analyzing co-located radiosondes, showing a good agreement. In a second stage, active remote sensing systems were used for deriving the PBLH. Thus, Extended Kalman filter is applied to EL data while the vertical wind speed variance method was applied to the DL. The derived PBLH\'s by these approaches are compared to PBLH retrieved by the MWR. The results show a good agreement among the retrievals based on active remote sensing in most of the cases, although some discrepancies appear in instances of intense PBL changes (either growth and/or decrease). Then it is performed the analysis of four and five-year dataset of measurements gathered with a ceilometer and a microwave radiometer, respectively, at Granada. The methodologies applied for the PBLH detection (gradient method for ceilometer and the combination of parcel method and temperature gradient method for microwave radiometer) provided a satisfactory description of the PBL structure in simple cases. In addition, the PBL behavior is characterized by a statistical study of the convective and stable PBLH obtained from microwave radiometer measurements. The analysis of the PBLH statistical study shows some coincidence with other PBLH studies such as daily pattern, and year cycles but also some differences caused by distinct latitudes, topography and climate were found. It was performed as well a combined long-term analysis of Ceilometer retrieved Residual Layer and the Stable and Convective Layer heights determined by microwave radiometer, thus offering a complete picture of the PBL evolution by synergetic combination of remote sensing techniques. This is the reason why systems with high temporal and spatial resolution, like lidars, have been increasingly applied in studies about this atmospheric region. In this work, also was performed, at São Paulo, an analysis on lidar backscattered signal at three wavelengths (355, 532 and 1064 nm) retrieving the turbulence by the analyses of the high-order moments (variance, skewness and kurtosis) in the backscattered signal. The wavelength of 355 nm has low applicability in the proposed methodology, due to its low intensity (due to predominance of molecular backscattering) and large presence of noise, while the 532 nm wavelength showed results similar to those provided by the wavelength of 1064 nm, which was used as reference. Then, it was analyzed two case studies using the wavelengths of 532 and 1064 nm (in separately). This approach provided information about PBL height, (derived by the variance method (Menut et al., 1999), displacement of aerosol layers (skewness) and level of mixing at several heights (kurtosis). These results show the viability of the proposed methodology when the wavelengths of 532 and 1064 nm are used for the PBL description by high-order moments of the backscattered distribution. Furthermore, it is demonstrated how some variables (air temperature, aerosol concentration, vertical wind, relative humidity and net radiation) can influence the PBL dynamic with data from DL, EL and MWR at Granada. The high-order moments of the vertical velocity high frequency distributions derived from DL, and EL range corrected signal, were corrected by two methodologies (first lag and -2/3 correction). The corrected profiles present small differences when compare against the uncorrected profiles, showing low influence of noise and the viability of the proposed methodology. A detailed 2-case studies analysis was carried on, the first case corresponding to a well-defined PBL while the second one corresponds to a situation with presence of an aloft Saharan dust layer and clouds. In both cases the results provided by the different instruments ended up complementing one another, so that the synergistic use of the different systems allowed us a detailed monitoring of the PBL.